2005
DOI: 10.1111/j.1399-6576.2005.00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety of mixture of morphine with ketamine for postoperative patient‐controlled analgesia: an audit with 1026 patients

Abstract: Patient-controlled analgesia with morphine and ketamine is safe. It produces side-effects which, however, are infrequently a reason for discontinuing the regimen. It is also associated with low pain scores and high patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…15,16 Animal and clinical studies demonstrate that acute opioid tolerance can be prevented by co administration of NMDA receptor antaogonist 9,17 as shown in our study by adding just 250 µg/kg of ketamine to 15 µg/kg of morphine in postoperative patients. Weinbroum et al (2003) 17 found that subjectively evaluated pain in intensity during the 2 hour PACU stay was significantly lower for MK patients as compared to their MS counterparts despite large amounts of morphine administered.…”
Section: Resultsmentioning
confidence: 91%
“…15,16 Animal and clinical studies demonstrate that acute opioid tolerance can be prevented by co administration of NMDA receptor antaogonist 9,17 as shown in our study by adding just 250 µg/kg of ketamine to 15 µg/kg of morphine in postoperative patients. Weinbroum et al (2003) 17 found that subjectively evaluated pain in intensity during the 2 hour PACU stay was significantly lower for MK patients as compared to their MS counterparts despite large amounts of morphine administered.…”
Section: Resultsmentioning
confidence: 91%
“…[14][15][16][17][18][19][20][21][22]24 This, and the fact that the same analgesic effect can be achieved with lower doses (up to 30% to 40% lower) using this same administration route-thereby contributing to a lessening of side effects as compared with the parenteral route 21 -led us to apply this management protocol to our patient.…”
Section: Discussionmentioning
confidence: 95%
“…13 On the other hand, the drug has also been shown to be very effective in patients with severe neuropathic pain secondary to other causes: oncological pain, 14 pain of central origin secondary to stroke, 15 chronic neuropathic pain of spinal origin, 16 postherpetic neuralgia, 17 phan- 21 and postoperative pain. 22 However, we have found no reference in the literature of the clinical use of oral ketamine in patients with CRPS. The most frequent adverse effects of ketamine involve the central nervous system, and include cognitive dysfunction, dizziness, visual hallucinations, nightmares, and even pseudo-psychiatric disorders 15 though none of these problems was recorded in our case.…”
Section: Discussionmentioning
confidence: 98%
“…Some authors have shown that low dextroketamine doses associated to morphine potentiate analgesia and decrease opioids adverse effects, as well as its ability to decrease pain scores 9 . A large prospective study has shown safety of intravenous dextroketamine and morphine for patient--controlled analgesia 10 . In a systematic review of ketamine for postoperative analgesia, authors have concluded that intravenous ketamine is an effective adjuvant, decreases opioid consumption, improves pain control quality, with special benefits for more painful procedures, such as high abdominal surgeries, thoracotomies and major orthopedic interventions 11 .…”
Section: Discussionmentioning
confidence: 99%